Samosir Regency in the Development of Monument - Corry; Resna Napitu; Supsiloani; Ulung Napitu (SIASAT, 2020)
This study aims to discuss the development of monument in Samosir Regency, North Sumatra, Indonesia by using a descriptive analytic method with a phenomenological approach. The phenomenological approach is a tradition of qualitative research that is rooted in philosophical and psychological, and focuses on the experience of human life (sociology). The results of this study indicate that there are so many public opinions regarding the development of the monument carried out by Toba Batak community in Samosir Regency. However, the development of this monument is inseparable from two aspects, namely in terms of religion / belief and cultural aspects. The development of monument that is so fierce in Samosir Regency carries so many meanings behind the monument itself. The number of parsadaan’s monument in Samosir Regency is 19.